Direct membrane filtration of municipal wastewater: linking periodical physical cleaning with fouling mechanisms - Hube, Selina (2022)
Direct membrane filtration (DMF) is a promising alternative secondary wastewater treatment process in Iceland, where biological treatment is not effective due to low strength wastewater nature and low temperature. This study aims to investigate membrane fouling mechanisms and mitigation approaches during DMF of municipal wastewater using a crossflow membrane filtration system integrated with an optical coherence tomography (OCT) imaging system. During DMF of wastewater, it was observed that intermediate pore blocking was dominant during the early stage of fouling, followed by cake filtration. Multi-filtration cycles were performed under different conditions, and the results revealed that (1) elevating flushing water temperature from 25 to 50 °C greatly reduced the intermediate pore blocking constant accompanied with a decreased physically-irreversible fouling; (2) increasing both filtration and flushing crossflow velocities did not influence the pore blocking constant, but caused a lower cake filtration constant with reducing both physically-reversible and irreversible fouling; (3) extending filtration-flushing duration interval appeared to slightly lower the pore blocking constant; (4) with extending filtration cycles, a shift of reversible fouling to irreversible fouling was noticed and associated with the compression of the tightly attached cake layer that was not readily removed by periodical flushing. A combination of periodical physical flushing with short term chemical-enhanced cleaning was employed and sustainable long-term operation of DMF was achieved. Furthermore, the foulants autopsy indicated that biofouling combined with organic/inorganic fouling influenced the cake fouling development.